Komunikasi Terapeutik Orang Tua Dalam Membentuk Karakter Positif Anak Sindrom Down Di Kenegerian Teluk Kuantan Riau - Zahratul Aini; Evawani Elysa Lubis (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2023)
Therapeutic communication is communication that has the aim of healing. Down syndrome is a chromosomal abnormality that is inherited from birth. This research aims to determine the process of therapeutic communication, therapeutic communication techniques and barriers to therapeutic communication carried out by parents in shaping the positive character of children with Down syndrome in Kenegerian Teluk Kuantan. The phenomenon raised began with observations made by researchers. This interest arose because of the differences in positive characteristics possessed by Down syndrome children in Kenegerian Teluk Kuantan. The differences in the positive characteristics of children with Down syndrome in Kenegerian Teluk Kuantan, Riau, are a unique and interesting phenomenon to study. Differences in age and parenting patterns of Down syndrome children in Kenegerian Teluk Kuantan can shape the character they have. The similarities they have make them unique. This research uses descriptive qualitative methods. The subjects of this research were 12 people, namely children with Down syndrome, parents or guardians and neighbors around where the children with Down syndrome lived in Kenegerian Teluk Kuantan. Taking place in Kenegerian Teluk Kuantan, Riau. The data collection techniques used in this research were observation, interviews and documentation. This research lasted 7 months starting from September 2022 to February 2023. The results of this research show that therapeutic communication carried out by parents can shape the positive character of children with Down syndrome in terms of their independence. The independence of Down syndrome children in Kenegerian Teluk Kuantan includes politeness towards others, such as being able to say sorry, thank you and please. Independence in taking care of yourself, such as being able to shower yourself, iron your own clothes, wash your own clothes. Can treat others well. Smartphones are the best friends for children with Down syndrome in Kenegerian Teluk Kuantan, Riau. Parenting styles play an important role in the development of children with Down syndrome. The development of Down syndrome children also makes the age difference a benchmark for the independence of Down syndrome children in Kenegerian Teluk Kuantan.